2017
DOI: 10.1016/j.neuron.2017.08.025
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine Neurons Respond to Errors in the Prediction of Sensory Features of Expected Rewards

Abstract: Summary Midbrain dopamine neurons have been proposed to signal prediction errors as defined in model-free reinforcement learning algorithms. While these algorithms have been extremely powerful in interpreting dopamine activity, these models do not register any error unless there is a difference between the value of what is predicted and what is received. Yet learning often occurs in response to changes in the unique features that characterize what is received, sometimes with no change in its value at all. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
187
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 178 publications
(211 citation statements)
references
References 52 publications
24
187
0
Order By: Relevance
“…2A and B) was almost the inverse of that of DA neurons recorded in the same task (Takahashi et al, 2017). In our hands in this task, DA neurons begin to respond about 100 ms after reward delivery and peak 200–300 ms after each reward drop, whereas the OFC neurons began to respond before each drop of reward, peaked about 100 ms after delivery, and reached a local minimum 250–300 ms after reward delivery.…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…2A and B) was almost the inverse of that of DA neurons recorded in the same task (Takahashi et al, 2017). In our hands in this task, DA neurons begin to respond about 100 ms after reward delivery and peak 200–300 ms after each reward drop, whereas the OFC neurons began to respond before each drop of reward, peaked about 100 ms after delivery, and reached a local minimum 250–300 ms after reward delivery.…”
Section: Resultsmentioning
confidence: 79%
“…Previously we have described how neurons in this dataset fired to the predictive cues (Stalnaker et al, 2014); here we focused on the firing in anticipation of and just after delivery of each drop of reward, looking specifically for differences in firing based on whether the reward number or flavor was unexpected or expected. Unlike dopamine neurons recorded in this setting, which exhibited phasic error-like responses after surprising changes in either reward number or reward flavor (Takahashi et al, 2017), OFC neurons showed no such error correlates and instead fired in a way that reflected reward predictions. …”
mentioning
confidence: 82%
See 1 more Smart Citation
“…That is, if a cue previously paired with a particular reward was unexpectedly presented with a different reward that was equally valuable, we would expect to see a prediction error in dopaminergic neurons. And in fact recent evidence has emerged to suggest dopamine does in fact encode such information (Takahashi et al, 2017). Specifically, Takahashi et al (2017) have shown that dopamine neurons exhibit their classic prediction-error signal to changes in the sensory properties of rewards that are equally prefered.…”
Section: Where To Now?mentioning
confidence: 99%
“…And in fact recent evidence has emerged to suggest dopamine does in fact encode such information (Takahashi et al, 2017). Specifically, Takahashi et al (2017) have shown that dopamine neurons exhibit their classic prediction-error signal to changes in the sensory properties of rewards that are equally prefered. That is, dopamine neurons show errors to the change in reward identity without a change in reward value.…”
Section: Where To Now?mentioning
confidence: 99%